2021
DOI: 10.1016/j.isci.2021.102758
|View full text |Cite
|
Sign up to set email alerts
|

ERAD components Derlin-1 and Derlin-2 are essential for postnatal brain development and motor function

Abstract: Derlin-1 and Derlin-2 are essential for postnatal brain development and function Chemical chaperon does not ameliorate the phenotype of Derlindeficient neuron Derlin regulates SREBP-2 activation and promotes brain cholesterol biosynthesis Derlin-mediated cholesterol biosynthesis is essential for neurite outgrowth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
(52 reference statements)
2
19
0
Order By: Relevance
“…Derlin-1 is implicated in ERAD and interacts with misfolded transmembrane proteins during their transfer from the ER to the cytosolic proteasome [ [27] , [28] , [29] , [30] ]. To determine whether p22 phox mutant proteins bind to Derlin-1, Derlin-1–FLAG proteins were immunoprecipitated from the cell lysates of CHO–K1 cells expressing exogenous p22 phox –Myc and Derlin-1–FLAG proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Derlin-1 is implicated in ERAD and interacts with misfolded transmembrane proteins during their transfer from the ER to the cytosolic proteasome [ [27] , [28] , [29] , [30] ]. To determine whether p22 phox mutant proteins bind to Derlin-1, Derlin-1–FLAG proteins were immunoprecipitated from the cell lysates of CHO–K1 cells expressing exogenous p22 phox –Myc and Derlin-1–FLAG proteins.…”
Section: Resultsmentioning
confidence: 99%
“…They are then degraded by the ubiquitin–proteasome system [ 43 ]. Derlin-1 is part of a channel for retro-translocation and is essential for the degradation of misfolded membrane proteins [ [27] , [28] , [29] , [30] ], such as cystic fibrosis transmembrane conductance regulator (CFTR)-ΔF508 mutant protein [ 44 , 45 ]. Herein, we demonstrated that in the ER, the substitution of Leu-51, Leu-52, Glu-53, and Pro-55 facilitates the interaction of p22 phox with Derlin-1 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, among the 39 common mRNAs targets for miR-133a-3p and miR-106b-5p, there is a DERL2 gene, encoding for Derlin-2 protein, one of the endoplasmic reticulum (ER) membrane proteins and part of the ERAD degradation complex which eliminates unfolded proteins [ 38 ]. Recent findings by Sugiyama et al demonstrated that Derlin-2-deficient mice have widespread postnatal brain atrophy in the cerebellum and striatum as well as reduced neurite outgrowth and motor function deficits [ 39 ]. We can hypothesize that a generalized downregulation of miRNAs observed in lvPPA could lead to a translation upregulation and an alteration of target gene expression [ 40 ] and vice-versa in svPPA.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of SCAP protein in the brain affects brain morphology and neuronal activity, indicating that proper cholesterol content is important for brain homeostasis [48]. In addition, it has been reported that mice with central nervous system‐specific ablation of Derl‐1 , which encodes Derlin‐1 that is essential for ER quality control, exhibited brain atrophy and motor dysfunction due to suppression of SREBP2‐mediated cholesterol biosynthesis [49]. These reports are consistent with the phenotypes observed in the GPHR f/f ;Nes mouse brain.…”
Section: Discussionmentioning
confidence: 99%